Production of a New d-Amino Acid Oxidase from the Fungus Fusarium oxysporum - Gabler, Matthias (American Society for Microbiology, 1999)
The fungus Fusarium oxysporum produced a d-amino acid oxidase (EC 1.4.3.3) in a medium containing glucose as the carbon and energy source and ammonium sulfate as the nitrogen source. The specific d-amino acid oxidase activity was increased up to 12.5-fold with various d-amino acids or their corresponding derivatives as inducers. The best inducers were d-alanine (2.7 μkat/g of dry biomass) and d-3-aminobutyric acid (2.6 μkat/g of dry biomass). The addition of zinc ions was necessary to permit the induction of peroxisomal d-amino acid oxidase. Bioreactor cultivations were performed on a 50-liter scale, yielding a volumetric d-amino acid oxidase activity of 17 μkat liter(−1) with d-alanine as an inducer. Under oxygen limitation, the volumetric activity was increased threefold to 54 μkat liter(−1) (3,240 U liter(−1)).